Jakość życia - między wolnością a mistyfikacją - Adamiec, Marek; Popiołek, Katarzyna (Wydział Prawa i Administracji UAM, 1993)
The concept of t he quality of life presented in the article can be most adequately characterized as an attempt of an individual to implement his/her own way of living. Such an implementation has two aspects. The first can be reduced to external conditions making it possible to realize so-called generative values (external quality of living). The second aspect is treated as a possibility of attaining and expressing human personality. Basic statements of the conception have been illustrated by the characteristics of the quality of life of the unemployed.
Quality of life - between freedom and mistification